(untitled) (Research, Society and Development, 2022)
Classical Genetics and Molecular Biology are disciplines of great importance within the curriculum of Higher Education courses linked to Biological Sciences. Because it contains many abstract terms and mechanisms, most students report some difficulty in effectively understanding the topics covered. In this way, many authors highlight the importance of using didactic models to facilitate the learning of complex themes, making classes more attractive, in addition to promoting the inclusion of students with special needs, such as those with visual impairments and deficits in Warning. The didactic model created uses simple and low-cost materials (such as styrofoam balls, biscuit dough, cords and ropes), which allows the teacher to work on the topic of Compaction levels of eukaryotic genetic material, in addition to the approach of the theme of Epigenetics (chromatin remodeling mechanisms), which is much discussed nowadays. We believe that the use of the proposed didactic model can positively impact students learning, enabling a better contextualization and visualization of the aforementioned topics, applied in the disciplines of Classical Genetics and Molecular Biology, in Higher Education.